Review of possible mechanisms of radiotherapy resistance in cervical cancer - Zhang, Hanqun; Wang, Xiaohu; Ma, Yan; Zhang, Qiuning; Liu, Ruifeng; Luo, Hongtao; Wang, Zi (Frontiers in Oncology, 2023)
Radiotherapy is one of the main treatments for cervical cancer. Early cervical cancer is usually considered postoperative radiotherapy alone. Radiotherapy combined with cisplatin is the standard treatment for locally advanced cervical cancer (LACC), but sometimes the disease will relapse within a short time after the end of treatment. Tumor recurrence is usually related to the inherent radiation resistance of the tumor, mainly involving cell proliferation, apoptosis, DNA repair, tumor microenvironment, tumor metabolism, and stem cells. In the past few decades, the mechanism of radiotherapy resistance of cervical cancer has been extensively studied, but due to its complex process, the specific mechanism of radiotherapy resistance of cervical cancer is still not fully understood. In this review, we discuss the current status of radiotherapy resistance in cervical cancer and the possible mechanisms of radiotherapy resistance, and provide favorable therapeutic targets for improving radiotherapy sensitivity. In conclusion, this article describes the importance of understanding the pathway and target of radioresistance for cervical cancer to promote the development of effective radiotherapy sensitizers.